Central Florida: growing green - Kern, Kelsey (Kansas State University, 2009)
The growth of Central Florida led to the planning of a Central Florida commuter rail and a larger interest in designing communities with the environment as a priority. A site suitable for sustainable development is located in DeBary, Florida, in the northern Orlando metropolitan area. The nine hundred acre site includes a commuter rail station and is located along the St. Johns River, a major river in Florida. The intent of this study was to understand and apply principles of sustainable development to the unique landscape of the site and propose a master plan for a community, creating a sense of place. A major goal of the project was to compliment the commuter rail station and its contribution to the community. The project encompassed research of sustainable development and design, an analysis of the site, as well as an understanding of transportation’s specific role in sustainable development. The result of the study is a master plan of the community which utilizes principles of sustainable development, protects and highlights the ecological features of the site and creates a place unique to Central Florida as a healthy, sustainable community.
Keywords: Sustainable development; Sustainable design; DeBary Florida; Community design; Transportation; Landscape Architecture (0390)